Rhabdomyolysis due to Lamivudine administration in acute viral hepatitis B infection: a case report from Malaysia - Baharin, Janudin; Sulaiman Sahari, Narisa; Mohd Sazlly Lim, Sazlyna (Electronic Physician, 2014)
Rhabdomyolysis is a serious but rare side effect of Lamivudine treatment. Therefore, appropriate biochemical monitoring should be undertaken when it is used in the treatment of hepatitis B. This paper presents a case of Lamivudine-associated rhabdomyolysis in a 31-year-old man with congenital heart disease and hepatitis B. Three days after starting Lamivudine, the patient developed myalgia. Significant muscle tenderness and swelling of the upper and lower limbs was discovered during a physical examination. Creatine kinase was markedly raised. Lamivudine-induced rhabdomyolysis was suspected and the drug was discontinued. Symptoms and creatine kinase activity improved within four days of Lamivudine cessation and hydration. Early identification of Lamivudine-induced rhabdomyolysis is key in preventing this potentially fatal drug reaction; withdrawal of Lamivudine may contribute to complete remission of rhabdomyolysis.